Crises and Opportunities of Married Students: A Study of Rajshahi University - Hossan, Md. Alomgir; Md. Burhan Uddin Milon; Md. Rashel Ahamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The number of married students pursuing higher education is increasing, yet academic research often overlooks their experiences. This study addresses the gaps, such as mental condition, academic achievements, and career successes, by investigating the multifaceted crises and opportunities associated with combining marriage and higher education. This study aims to identify the major crises and opportunities involved, detailing the specific challenges related to time management, finances, social support, communication, and mental/physical health experienced by married students, explore the interplay between these factors, and investigate the strategies employed by the students to navigate these challenges. This study employed a quantitative method approach, and the 54 samples were collected through questionnaires from married students at the University of Rajshahi. Descriptive analysis techniques are applied to quantitative data methodologies in data analysis. Findings revealed that financial strain, social and mental pressure, academic difficulties, and familial responsibilities are major Problems. This study underscores the need for universities to implement supportive interventions, such as enhanced financial aid and flexible course scheduling, to provide better support for married students. The findings contribute to a more nuanced understanding of the complexities of student life and inform the development of effective support strategies.